RANCANGAN SISTEM INFORMASI BERBASIS HUMAN RESOURCES ANALYTICS PT. BANK X - Andrew Harnadi; Theresia Gunawan; Agus Gunawan (Jurnal Administrasi Bisnis, 2022)
PT. Bank X is a bank that has customers in Indonesia, which makes this bank on a local scale that only has branch offices in Indonesia. Banks with local scale have limited products such as loans and deposits. In the Covid-19 period, most Indonesian citizens preferred to save money and the consumptive rate decreased. This causes customers who want to save money also increase. Bank X requires to improve the performance of marketing staff by providing proper training. The research objective is to design an information system based on human resources analytics that can recommend appropriate training for marketing staff. This study uses descriptive analytical research types and case study research methods. The data collection was obtained through interviews, focus group discussion, and observations on information systems, developments and problems faced by PT. Bank X. Data analysis techniques use BPMN to describe the actual process that already exists and the proposed improvements for PT.Bank X. The results show information systems design based on HRA, which can recommend marketing staff who will be given training with the competencies required by the company. With this information system design, it is expected that companies can provide investment training to the right marketing staff.